Sociological Practice - Bruhn, John G. author. aut Link
XIV, 240 p. 27 illus.
Keywords: The second edition of this text focuses on how to plan, carry out, analyze, and evaluate interventions at the micro, meso, and macro levels. A sociological practitioner enters into a working relationship with clients to address social problems. The practitioner works with members of a client system to define the specific changes necessary and together they work to construct new social arrangements that will solve or reduce the impact of the problem. This text outlines and illustrates, with the help of Application Boxes, figures and tables, various approaches to problem-solving. It discusses the various steps in problem-solving from problem assessment, development of objectives and targets for change, to the implementation and evaluation of interventions. A final chapter is devoted to an examination of how principles of ethics apply at different levels of intervention and some of the ethical issues in sociological practice. The book is primarly written for sociology students at the upper division and graduate levels, but it should also be of interest to applied sociologists who teach, conduct research, and practice their discipline in a variety of contexts. The text could also be useful in the fields of social work, public administration , planning, criminal justice, and to organizational consultants.